Jak1/Stat3 Activation Alters Phosphate Metabolism Independently of Sex and Extracellular Phosphate Levels - Nicole Gehring (Kidney & Blood Pressure Research, 2021)
Introduction: Phosphate homeostasis is regulated by a complex network involving the parathyroid hormone (PTH), fibroblast growth factor 23 (FGF23), and calcitriol acting on several organs including the kidney, intestine, bone, and parathyroid gland. Previously, we showed that activation of the Janus kinase 1 (Jak1)-signal transducer and activator of transcription 3 (Stat3) signaling pathway leads to altered mineral metabolism with higher FGF23 levels, lower PTH, and higher calcitriol levels. Here, we investigated if there are sex differences in the role of Jak1/Stat3 signaling pathway on phosphate metabolism and if this pathway is sensitive to extracellular phosphate alterations. Methods: We used a mouse model (Jak1S645P+/−) that resembles a constitutive activating mutation of the Jak1/Stat3 signaling pathway in humans and analyzed the impact of sex on mineral metabolism parameters. Furthermore, we challenged Jak1S645P+/− male and female mice with a high (1.2% w/w) and low (0.1% w/w) phosphate diet and a diet with phosphate with organic origin with lower bioavailability. Results: Female mice, as male mice, showed higher intact FGF23 levels but no phosphaturia, and higher calcitriol and lower PTH levels in plasma. A phosphate challenge did not alter the effect of Jak1/Stat3 activation on phosphate metabolism for both genders. However, under a low phosphate diet or a diet with lower phosphate availability, the animals showed a tendency to develop hypophosphatemia. Moreover, male and female mice showed similar phosphate metabolism parameters. The only exception was higher PTH levels in male mice than those in females. Discussion/Conclusion: Sex and extracellular phosphate levels do not affect the impact of Jak1/Stat3 activation on phosphate metabolism.